Arhangelskii’s α-principles and selection games - Clontz, Steven (Topology Proceedings, 2020)
Arhangelskii’s properties α2 and α4 defined for convergent sequences may be characterized in terms of Scheeper’s selection principles. We generalize these results to hold for more general collections and consider these results in terms of selection games.